2022
DOI: 10.1007/s10792-022-02523-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Demodex folliculorum and Demodex brevis in patients with blepharitis and chalazion

Abstract: Purpose: Demodex folliculorum and Demodex brevis are common ectoparasites on skin that also can lead to blepharitis and chalazion. The aim of our study is to determine the prevalence of Demodex spp. in eyelashes of patients diagnosed with chronic blepharitis and chalazion.Methods: This study included 330 patients diagnosed with chronic blepharitis, 70 patients diagnosed with chalazion and 130 volunteers without any ocular problems. Patient eyelashes were examined under a light microscope at magni cations of × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…9,10 In addition, the presence of Demodex folliculorum mites on the eyelid margin is another known pathogenic risk factor for blepharitis. 11,12 A recent study by Akkucuk et al 13 reported that 75.5% of patients with blepharitis had Demodex folliculorum, which may be identified clinically by the pathognomonic sign of collarettes at the eyelash base. 14,15 As blepharitis progresses, meibomian gland dropout and cicatricial eyelid changes can occur.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In addition, the presence of Demodex folliculorum mites on the eyelid margin is another known pathogenic risk factor for blepharitis. 11,12 A recent study by Akkucuk et al 13 reported that 75.5% of patients with blepharitis had Demodex folliculorum, which may be identified clinically by the pathognomonic sign of collarettes at the eyelash base. 14,15 As blepharitis progresses, meibomian gland dropout and cicatricial eyelid changes can occur.…”
Section: Introductionmentioning
confidence: 99%